Public Policy and Market Mediation in Indian Higher Education - Varghese , N V (International Higher Education, 2025)
A new education policy reflects India’s efforts to reposition the sector within a changing context and its aspiration to develop the country as a global higher education hub. The policy proposals for the universalization and internationalization of higher education, and for the restructuring of curriculum, reinforce these perspectives. Although the institutional framework for policy implementation is not yet fully in place, a shift in orientation toward centralization, market mediation, and a reduced reliance on public institutions seems core to the reforms.